Peran Dinas Koperasi UMKM Kota Medan Dalam Mewujudkan Program Masjid Mandiri Melalui Koperasi Syari’ah - Zulfahani Zulfahani; Zuhrinal M. Nawawi (El-Mujtama: Jurnal Pengabdian Masyarakat, 2022)
This study aims to determine and analyze the role of the Medan City Umkm Cooperative Service in realizing an independent mosque program through the Syari'ah Cooperative. This study uses a qualitative method where this research method is to understand social or human events by creating a comprehensive and complex picture that can be presented in words, reporting detailed data from informant sources. The result of this research is a new program from the Pemko Medan which is named the Mandiri Mosque, this is very useful because the mosque apart from being a place of worship can also be used as a forum for the economy. With the aim that if this program is successful, it will become a strong and good foundation for us to help the people. Keywords: Role, Independent Mosque, Sharia Cooperative